Pengaruh Terpaan Informasi Keluarga Berencana terhadap Intensi Penggunaan Metode Kontrasepsi Jangka Panjang - Kholidil Amin; Purwanti Hadisiwi; Jenny Ratna Suminar; Susanne Dida (Program Studi Ilmu Komunikasi, 2022)
Family Planning (FP) is a program continuously promoted by the Government of Indonesia to control population growth. One of the government's efforts is to increase long-acting contraceptive methods (LAPM). Information about FP and LAPM is important for couples of childbearing age deciding on contraceptive method choice. This research uses the theory of planned behavior, and the present study examines the effect of information exposure about FP on intentions to use LAPM, mediated by several factors forming behavioral intentions. The present study conducted a cross-sectional survey of 74 women of childbearing age in Kampung KB RW01 Pringgokusuman, Yogyakarta City. PLS-SEM (Structural equation modeling) was employed to test the model's fit and path analysis. The present research found that information exposure to FP predicts attitudes, subjective norms, and perceived behavioral control related to LAPM. The results also showed that the intention to use LAPM is significantly influenced by information exposure about FP mediated by subjective norms but not mediated by attitude and perceived behavioral control. The present study also discusses the implications of these findings for the theoretical realm and the practical domain of FP.